SAT0052 Influence of Immunogenicity and Drug Levels on the Efficacy of Long-Term Treatment of Rheumatoid Arthritis with Adalimumab and Etanercept: A Uk-Based Prospective Study. (10th June 2014) - Jani, M.; Chinoy, H.; Warren, R.B.; Fu, B.; Griffiths, C.E.; Morgan, A.W.; Wilson, G.; Hyrich, K.L.; Isaacs, J.D.; Barton, A.
Abstract : Background: The introduction of tumour necrosis factor inhibitors represents a major advance in the treatment of rheumatoid arthritis (RA). Despite this, up to 40% of patients fail to respond- either due to primary inefficacy or loss of response. One explanation is immunogenicity leading to the development of anti-drug antibodies (ADAb) and low drug levels. Radioimmunoassay (RIA) is a sensitive method to detect ADAb and is less prone to drug interference vs . ELISA. The clinical utility of pharmacological monitoring in routine rheumatology practice is still debated with conflicting opinions. Objectives: To evaluate whether ADAb formation and serum drug levels may predict future treatment response of anti-TNF initiated RA patients. Methods: 331 patients were selected from the Biologics in RA Genetics and Genomics Study Syndicate prospective cohort [n=160 adalimumab (AD); n=171 etanercept (ETA)]. Serum samples were collected at 3, 6 and 12 months following initiation of therapy. ADAb were measured using RIA and drug levels using ELISA at 3, 6 and 12 months; the timing of blood samples was not consistently pre-dose. Disease activity (DAS28) scores were measured at each visit. Descriptive statistics, multiple linear regression and generalised estimating equation were used as appropriate. Results: 835 serial samples were suitable for pharmacological testing (n=414 AD; n=421 ETA). Mean age: 56±13 years; 75% female; baseline DAS28 score 5.9±0.8; median BMI 27.5 (IQR 23.6-32.3). 85% were on a DMARD (56% MTX). ADAbs to AD were detected in 24.8% (31/125 patients at ≥1 time points by 12 months) and in none of the ETA patients. The presence of ADAbs were significantly associated with lower AD drug levels ( p <0.0001; rs -0.51; if ADAb titres>100AU p =0.0041; rs -0.66). At 3 months, ADAb formation and low drug levels were a significant predictor of poor ΔDAS28 at 6 and 12 months ( p <0.0001, RC -0.0048 95% confidence intervals (CI) -0.0071 to -0.0025). By 12 months, patients who developed ADAbs showed less improvement in disease activity (mean ΔDAS28 2.35; CI 1.67-3.03) than patients without (mean ΔDAS28 3.15; CI 2.86-3.35; p =0.022). Patients who did not develop ADAbs were more likely to be co-treated with MTX (61.4% vs. 43.7% p =0.01). AD drug level was the most significant independent predictor of ΔDAS28 at all time points after adjusting for confounders ( p <0.0001, RC 0.12, CI: 0.06-0.18). At 12 months, patients on ETA with higher drug levels (>15μg/mL) were more likely to achieve a good EULAR response than patients with sub-therapeutic levels (<0.0035 μg/mL) ( p =0.01). High BMI was the strongest predictor of low drug levels (ETA, p <0.0001, RC -5.97; CI -8.75 to -3.19; AD, p <0.0001, RC-3.86; CI -5.72 to -2.00). Conclusions: At 3 months ADAb formation and low AD drug levels are a significant predictor for poor treatment response at 6 and 12 months. In addition low AD drug levels were the strongest independent predictor of poor treatment response at all time points. Acknowledgements: Supported by Medical Research Council [grant number G1000417/94909], Arthritis Research UK [20385] and NIHR Manchester Musculoskeletal BRU. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3811